Orion Gizzi: capstone - Gizzi, Orion, artist (Colorado State University. Libraries, 2022)
The artist's statement: For this series of artwork, I focused on how gender dysphoria affects me in my life. I am a transgender individual and gender dysphoria something I experience on an almost day to day basis; this causes me to have a lot of mixed emotions about how I feel about and in my own body such as insecurity, frustration, dissatisfaction, and embarrassment. I wanted to explore the ways in which how I feel about typically gendered situations has changed the further along in my transition I get; focusing mainly on prom and weddings. These situations are seen to have a more feminine connotation to them and are events in which clothing takes on a more gendered structure. Imagery such as dresses, flowers, cake decorations, and the color pink tend to also be seen as more feminine, which is why I have included those in my artwork. I also took inspiration from contemporary artists who incorporate cake piping tools to create textured paint that protrudes from the canvases. I used the cake piping technique in my own art to create the 3D floral decorations in Self Portrait and Prom Dress. Events like my prom and my future self’s wedding – a day that I used to dream of being a princess on – now no longer feel so special. There’s new feelings of discomfort and uncertainty about them now because wearing a dress and being viewed as a girl causes me gender dysphoria. My goal was to use very muddied and harsh colors on the wedding dress to display the feelings of discomfort and bitterness towards the conflict of no longer getting the chance to be the bride i dreamed of being as a kid, but also no longer wanting it. Since this project focuses mainly on internal feelings about my body, I felt that it was important to also be able to put the artwork on my body and wear it around. Painting on dresses allowed me to express these feelings in a true-to-life size. In addition, I wanted the painting of the bridal portrait to feel almost daunting and larger than life with how big it is. I wanted this to emulate the overbearing feeling of gender dysphoria.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting